Does Processing or Formation of Water Ice Mantles Affect the Capacity of Nanosilicates to Be the Source of Anomalous Microwave Emission? - Mariñoso Guiu, Joan; Ferrero, Stefano; Macià Escatllar, Antonio; Rimola, Albert; Bromley, Stefan T. (Frontiers in Astronomy and Space Sciences, 2021)
The anomalous microwave emission (AME) is detected in many astrophysical environments as a foreground feature typically peaking between 20 – 30 GHz and extending over a 10 - 60 GHz range. One of the leading candidates for the source of the AME is small spinning dust grains. Such grains should be very small (approx. ≤ 1 nm diameter) in order for the rotational emission to fall in the observed frequency range. In addition, these nanosized grains should possess a significant dipole moment to account for the observed emissivities. These constraints have been shown to be compatible with spinning bare nanosilicate clusters, assuming that ~1% of the total Si mass budget is held in these ultrasmall grains. Silicate dust can be hydroxylated by processing in the interstellar medium and is generally known to provide seeds for molecular water ice nucleation in denser regions. Herein, we use quantum chemical calculations to investigate how the dipole moment of Mg-rich pyroxenic (MgSiO3) nanoclusters is affected by both accretion of molecular water and dissociative hydration. Our work thus provides an indication of how the formation of water ice mantles is likely to affect the capacity of nanosilicates to generate the AME.